2003
DOI: 10.1128/jb.185.8.2548-2554.2003
|View full text |Cite
|
Sign up to set email alerts
|

Function and Regulation of the Formate Dehydrogenase Genes of the Methanogenic ArchaeonMethanococcus maripaludis

Abstract: Methanococcus maripaludis is a mesophilic species of Archaea capable of producing methane from two substrates: hydrogen plus carbon dioxide and formate. To study the latter, we identified the formate dehydrogenase genes of M. maripaludis and found that the genome contains two gene clusters important for formate utilization. Phylogenetic analysis suggested that the two formate dehydrogenase gene sets arose from duplication events within the methanococcal lineage. The first gene cluster encodes homologs of forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 26 publications
2
84
0
Order By: Relevance
“…In a previous study by Wood et al, our lab reported that either Fdh was sufficient for growth on formate, whereas a later study by Lupa et al reported that only Fdh1 supported growth on formate unless a ⌬fdh1 mutant was incubated for prolonged periods, ϳ70 h (15,35). This suggests that enrichment of a suppressor mutation may have accounted for the initial observations of Wood et al; the data in our present study agree with this interpretation.…”
Section: Discussionsupporting
confidence: 46%
“…In a previous study by Wood et al, our lab reported that either Fdh was sufficient for growth on formate, whereas a later study by Lupa et al reported that only Fdh1 supported growth on formate unless a ⌬fdh1 mutant was incubated for prolonged periods, ϳ70 h (15,35). This suggests that enrichment of a suppressor mutation may have accounted for the initial observations of Wood et al; the data in our present study agree with this interpretation.…”
Section: Discussionsupporting
confidence: 46%
“…maripaludis are selenoproteins (266); hence, the organism requires the presence of selenium to grow on formate (267,268). Genetic dissection has demonstrated that each homolog confers a competitive growth advantage, with single mutants impaired and double mutants unviable for formatotrophic growth (242). Interestingly, while some Methanosarcina species carry genes that encode Ffd homologs (269), methanogens with cytochromes cannot sustain formate-dependent growth.…”
Section: Ffd: F 420 -Reducing Formate Dehydrogenasementioning
confidence: 99%
“…This process is especially ecologically significant, given that formate produced by fermentative bacteria can be consumed by methanogens through interspecies transfer (244). It is well established that formatotrophic growth is linked to F 420 metabolism (17) and that it depends on F 420 -reducing formate dehydrogenases (called Ffd or Fdh) (242). Although Ffd has not been structurally characterized, biochemical studies on the enzyme from Methanobacterium formicicum (Mb.…”
Section: Ffd: F 420 -Reducing Formate Dehydrogenasementioning
confidence: 99%
See 1 more Smart Citation
“…A second Fdh (Fdh2; Mmp0138 -0139) was similarly regulated although not as markedly. The Fdhs reduce F 420 when formate instead of H 2 is the electron donor (12). The remaining genes that were markedly regulated by H 2 were those encoding F 420 -dependent methylenetetrahydromethanopterin dehydrogenase (Mtd; Mmp0372) and F 420 -dependent methylenetetrahydromethanopterin reductase (Mmp0058), central steps in methanogenesis.…”
Section: Distinct Effect Of H2 Limitation On Genes Encoding F420-depementioning
confidence: 99%